Effect Of Depth Of Ground Water On The Seismic Response Of Frame Type Buildings On Sand Deposits. Part I: Soil Response - Dikmen, S. Ümit; Kıymaz, Güven; TÜRK, AHMET MURAT (Springer, Po Box 17, 3300 Aa Dordrecht, Netherlands, 2009)
Earthquake codes often times classify the subsoil based on their shear wave velocities which are mostly calculated based on the situ static conditions. However, it has been shown by various researchers that saturated sands exhibit a softening behavior under cyclic conditions. As a result of this behavior the surface response may be significantly affected by the existence of ground water. In this study, the effect of depth of water table on the seismic response of sand deposits is investigated.
Keywords: seismic; sand; ground water; ground response; effective stress-analysis; 1994 northridge; liquefaction; earthquake; acceleration; California; sismik; kum; yeraltı suyu; zemin tepkisi; efektif gerilme analizi; sıvılaşma; deprem; hızlanma; Kaliforniya